Alignment-dependent strong-field ionization yields of carbonyl sulfide molecules induced by mid-infrared laser pulses. (28th September 2016) - Johansen, Rasmus; Bay, Kathrine Glerup; Christensen, Lauge; Thøgersen, Jan; Dimitrovski, Darko; Madsen, Lars Bojer; Stapelfeldt, Henrik
Abstract: Strong-field ionization of carbonyl sulphide (OCS) molecules, induced by a linearly polarized mid-infrared (mid-IR) probe laser pulse is investigated experimentally and theoretically. We focus on the dependence of the single-ionization yield on the alignment of the molecular axis with respect to the probe pulse polarization axis. In the experiment, the OCS molecules are 1-dimensionally adiabatically aligned and ionized by a 12-femtosecond pulse centered at 1850 nm. The alignment-dependent ionization yields are compared to the theory based on the two-step model for strong-field ionization. Overall the measurements are consistent with the theoretical results.